The Effects of Inorganic Fertilizer and Mineral Leucite Residues on K Uptake and Maize Yields (Zea mays L.) in Oxisols - Sri Hartati (Sains Tanah: Journal of Soil Science and Agroclimatology, 2018)
The purpose of this study was to determine the effect of inorganic fertilizer and leucite mineral residues on K uptake and maize yields. This research had been conducted from October 2016 to September 2017 in the experimental field of Neglasari, Dramaga, Bogor. The soil was analyzed in the Soil Chemistry and Fertility Laboratory of Sebelas Maret University, Surakarta. The study was arranged in a completely randomized block design using 11 treatments with three replications. The result showed that the NPK 150 kg ha-1 residues gave a better effect on corn yields whereas there was no significant effect of employing the standard NPK with RAE value of 123%. The study found that the residual treatment of inorganic fertilizers and leucite minerals had a significant impact on maize yields but not on K uptake.